Islam Pada Masa Dinasti Fathimiyah - Wasalmi Wasalmi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
History has recorded that the Fatimid dynasty was an Islamic dynasty that was born in the X century and had very brilliant achievements in Islamic civilization. In fact, this dynasty was able to compete with the two great dynasties at that time, namely the Abbasid dynasty in Baghdad and the Umayyad dynasty in Spain. The glory of Islam during the Fatimid dynasty, was very developed, prosperous in the economic field, educational institutions were built including: the great mosque of al-Azhar which became a university educational institution in Cairo, Dar al-'Ilmi as a center for the study of Islamic sciences, astronomy and medicine . Likewise in the field of architecture, starting from magnificent gates, paintings, carvings, textile and ceramic products. All this shows the existence of the Fatimid dynasty at that time.